Pertumbuhan setek tiga aksesi katuk (Sauropus androgynus (L.) Merr.) asal Bogor pada berbagai komposisi media tanam - Rahayu, Arifah; Nisa, Chairun; Yuliawati, Yuliawati (JURNAL AGRONIDA, 2025)
The use of basil leaves as a vegetable and biopharmaceutical plant requires products that are safe for consumption, thus encouraging environmentally friendly cultivation using natural fertilizers, especially as a nitrogen source. This research aims to determine the effect of various types of organic nitrogen source fertilizer on the growth and production of several basil accessions. The study was conducted in July-September 2021 at the Jambu Luwuk Ciawi, Bogor experimental field. The research design used was factorial CRD. The first factor was basil accessions (Kadudampit, Ciaruteun and Cidolog), and the second factor was the source of N (without N fertilizer, urea, kipahit (Tithonia diversifolia L.) compost, kirinyuh (Chromolaena odorata L.) compost, and chicken manure). The variables observed were the number of leaves, plant height, number of branches and total branch length, leaf area, stem diameter, fresh and dry weight of the first to third harvest, and fresh and dry weight of roots and shoots. The Kadudampit accession has advantages in plant height, leaf area, wet and dry weight of first and second harvest as well as dry weight of third harvest and total harvest compared to other basil accessions. The application of kirinyuh compost increased the height of the basil plants, while the use of chicken manure increased the number of leaves, branches, total branch length, and wet and dry weight of the shoot and roots of the basil. Kirinyuh compost and chicken manure can be alternative sources N as substitute for urea in basil plants.